Improvements in technology and the expanding role of time-driven, activity-based costing to increase value in healthcare provider organizations: a literature review - Etges, Ana Paula Beck Da Silva; Jones, Porter; Liu, Harry; Zhang, Xiaoran; Haas, Derek (Frontiers in Pharmacology, 2024)
This study evaluated the influence of using technology on accurately measuring costs using Time-Driven Activity-Based Costing (TDABC) in healthcare provider organizations by identifying the most recent scientific evidence of how it contributed to increasing the value of surgical care. This literature-based analysis mainly used two data sources: the most recent systematic review that specifically evaluated TDABC studies in the surgical field and all articles that mentioned the use of the software CareMeasurement (CM) to implement TDABC. The articles from the systematic review were grouped as manually performing TDABC, while those using CM were grouped as technology-based. A general description was followed by 3 levels of information extraction: sample of cases, number of articles published per year, and the contributions of TDABC to achieve cost savings or other improvements. Fourteen studies using real-world patient-level data to evaluate costs were composed of a manually-based group. All thirteen studies that reported the use of CM composed the technology-based group of articles. In the manually-based studies, the average sample of cases included per study was 160, while in the technology-based studies, the average sample of cases included was 4,767. Technology-based studies on average have a more comprehensive impact than the manual TDABC ones do in providing accurate cost information from larger samples.TDABC studies supported by technologies such as CM register expressive and larger sample cases, identify cost-saving opportunities, and are frequently used to support reimbursement strategies based on value. The findings suggest that using TDABC with the support of technology can increase healthcare value.